Digital versus traditional marketing for hotels - Briggs, Susan (Henry Stewart Talks, 2009)
Advantages of digital marketing over traditional media, How e-marketing is changing the way we do business, Website content and promotion, Monitoring effectiveness, New developments in e-marketing
Archived at 2022/04/07